Isolation and Biological Activities of Furanoflavones from the Roots of Codonopsis cordifolioidea - Leng, Hongqiong; Yang, Guangyu; Chen, Yongkuan; Guo, Yadong; Chen, Zhangyu (Asian Journal of Chemistry, 2012)
A new furanoflavone, cordifoliketone C (1), together with three known furanoflavones (2-4), were isolated from the roots of Codonopsis cordifolioidea. Their structures were determined by means of HRESIMS, extensive 1D and 2D NMR spectroscopic studies and chemical evidence. Compounds 1-4 were tested for their anti-HIV-1 activity and antitobacco mosaic virus activity, respectively. The results showed that compounds 1-4 have modest anti-HIV-1 activity and anti-tobacco mosaic virus activity, respectively.